Diversity and cytological studies of the Genus Amomum Roxb. former Elettariopsis Baker (Zingiberaceae) in Thailand - Surapon Saensouk; Piyaporn Saensouik (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saensouk P, Saensouk S. 2021. Diversity and cytological studies on the genus Amomum Roxb. former Elettariopsis Baker (Zingiberaceae) in Thailand. Biodiversitas 22: 3209-3218. A comprehensive diversity and cytological studies of the genus Amomum Roxb. in Thailand have not been reported. This work aims to study the diversity and cytological including chromosome numbers and karyotypes of the genus Amomum Roxb. former Elettariopsis Bakerin Thailand. Ten species of Amomum were recognized from Thailand. Nomenclatures, vernacular names, distribution, ecology, and traditional utilization are provided. Only Amomum wandokthong is widely cultivated in all parts in Thailand. Four living species, i.e. Amomum curtisii, A. monophyllum, A. trilobum, and A. wandokthong have been collected from field trips. Therefore, the somatic chromosome numbers from four species of this genus were studied from root tips. The somatic chromosome numbers of each species in this study were counted from 20 cells. The karyotype formulas were derived from measurements of the metaphase chromosomes in photomicrographs. The chromosome numbers of four species were found to be 2n = 48. Karyotypes of four species were reported to be Amomum curtisii (32m + 8sm + 8st), A. monophyllum (26m + 12sm + 10st), A. trilobum (18m + 24sm + 6st), and A. wandokthong (28m + 16sm + 4st with five visible satellites chromosomes). The chromosome numbers of A. monophyllum and A. wandokthong were reported for the first time. The karyotypes of four species were studied for the first time.